Upcycling Plastic Waste into High Value‐Added Carbonaceous Materials. Issue 1 (5th November 2021) - Choi, Jiho; Yang, Inchan; Kim, Sung‐Soo; Cho, Se Youn; Lee, Sungho
Abstract: Even though plastic improved the human standard of living, handling the plastic waste represents an enormous challenge. It takes more than 100 years to decompose discarded or buried waste plastics. Microplastics are one of the causes of significantly pervasive environmental pollutants. The incineration of plastic waste generates toxic gases, underscoring the need for new approaches, in contrast to conventional strategies that are required for recycling plastic waste. Therefore, several studies have attempted to upcycle plastic waste into high value‐added products. Converting plastic waste into carbonaceous materials is an excellent upcycling technique due to their diverse practical applications. This review summarizes various studies dealing with the upcycling of plastic waste into carbonaceous products. Further, this review discusses the applications of carbonaceous products synthesized from plastic waste including carbon fibers, absorbents for water purification, and electrodes for energy storage. Based on the findings, future directions for effective upcycling of plastic waste into carbonaceous materials are suggested. Abstract : Converting plastic waste into carbonaceous materials is one of excellent upcycling techniques. This review discusses carbonaceous products derived from plastic waste and their preparation processes. In addition, the author introduces some representative application fields of the plastic‐waste‐derived carbonaceous materials. Finally, future directions for the effective upcycling of plastic waste into carbonaceous materials are discussed.